2020
DOI: 10.1259/bjr.20190891
|View full text |Cite
|
Sign up to set email alerts
|

Application of monoexponential, biexponential, and stretched-exponential models of diffusion-weighted magnetic resonance imaging in the differential diagnosis of metastases and myeloma in the spine-Univariate and multivariate analysis of related parameters

Abstract: Objective: To explore the value of related parameters in monoexponential, biexponential, and stretched-exponential models of diffusion-weighted imaging (DWI) in differentiating metastases and myeloma in the spine. Methods: 53 metastases and 16 myeloma patients underwent MRI with 10 b-values (0–1500 s/mm2). Parameters of apparent diffusion coefficient (ADC), true diffusion coefficient (D), pseudo-diffusion coefficient (D*), perfusion fraction (f), the distribution diffusion coefficient (DDC), and intravoxel wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…In our study, we observed that V p changes occurred in spinal metastases from a wide variety of primary cancers. The Diffusion-weighted imaging is another widely used MRI sequence that can help differentiate between nonneoplastic and malignant lesions (19,20). For example, Xing et al (19) used math models of DWI to differentiate metastases and myeloma with receiver operating characteristic curves in the range of 0.7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we observed that V p changes occurred in spinal metastases from a wide variety of primary cancers. The Diffusion-weighted imaging is another widely used MRI sequence that can help differentiate between nonneoplastic and malignant lesions (19,20). For example, Xing et al (19) used math models of DWI to differentiate metastases and myeloma with receiver operating characteristic curves in the range of 0.7.…”
Section: Discussionmentioning
confidence: 99%
“…The Diffusion-weighted imaging is another widely used MRI sequence that can help differentiate between nonneoplastic and malignant lesions (19,20). For example, Xing et al (19) used math models of DWI to differentiate metastases and myeloma with receiver operating characteristic curves in the range of 0.7. Lee et al (20) differentiated Schmorl nodes from metastases with a receiver operating characteristic of 0.94.…”
Section: Discussionmentioning
confidence: 99%
“…The region of interest (ROI) was set in the lesion center where the cross-section showed the largest level of the tumor with an area of 30–100 mm 2 ( 11 , 19 ) and the solid components of the tumor were included avoiding the lesion edge, necrosis, bone cortex of vertebral bodies or attachments, and blood vessels. The analysis was performed independently by two radiologists (initials: ELZ, XYX) with more than 5 years of experience on the GE AW4.5 workstation, and the average of the ROI measurements for each parameter was taken as the final measurement result.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that the ADC slow and ADC fast values of malignant spinal tumors were significantly different from those of tuberculous spondylitis (all P < 0.05) ( 4 ). In addition, IVIM has certain clinical value in differentiating spinal metastasis from myeloma and atypical vertebral hemangiomas ( 11 , 12 ). IVIM-diffusion-weighted imaging (DWI) could allow the early diagnosis of ductal carcinoma in situ of the breast, and reduce the misdiagnosis and over-treatment of benign lesions ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, many studies have revealed that it is often difficult to distinguish spinal MM from metastases by standard MRI alone, especially for patients with multiple vertebral focal osteolytic lesions and other atypical manifestation ( 11 , 12 ). Many studies pointed out that advanced MRI including contrast-enhanced (DCE) MRI and diffusion-weighted imaging (DWI) MRI could help differential diagnosis in the two diseases ( 5 , 11 13 ). But relevant studies are still limited and their findings require further investigation.…”
Section: Introductionmentioning
confidence: 99%